Characterization of pathogenic bacteria and histopathological analysis of whiteleg shrimp (Litopenaeus vannamei) in pond and hatchery systems in Simpang Mamplam and Jangka Districts - Akmal Izwar; Anis Nugrahawati; Yusrizal Akmal; Syahirman Hakim; Rizkan Fahmi; Erlia Hanum (Acta Aquatica: Aquatic Sciences Journal, 2026)
This study aimed to characterize pathogenic bacteria and analyze the level of hepatopancreatic tissue damage in whiteleg shrimp (Litopenaeus vannamei) originating from pond and hatchery cultivation systems in Jangka and Simpang Mamplam Districts, Bireuen Regency. Shrimp samples were collected from two types of water locations that receive aquaculture waste runoff, namely estuarine stations (aquaculture pond effluent) and coastal marine stations (hatchery effluent). Bacterial analysis was carried out through isolation on agar media and identification of colony morphology and biochemical tests, while histopathological analysis was carried out on hepatopancreatic tissue using the Hematoxylin–Eosin (H&E) staining method with a semi-quantitative scoring system. The results showed that the identified pathogenic bacteria included Aeromonas hydrophila, Vibrio parahaemolyticus, Photobacterium damselae, Vibrio alginolyticus, and Vibrio vulnificus with densities ranging from 10³–10⁷ CFU. The highest bacterial density was found at the estuarine station, especially from the genus Vibrio. Histopathological analysis revealed various structural changes in hepatopancreas tissue, including cell lysis, vacuolization, hemocyte aggregation, tubular damage, and inflammatory responses. Histopathological scores at the estuarine station (3.67–4.00) indicated a more severe level of tissue damage compared to the marine station (2.67). Keywords: Hepatopancreas; Histopathology; Litopenaeus vannamei; Pathogenic Bacteria; Vibrio